Can the green credit policy enhance firm export quality? Evidence from China based on the DID model - Yang, Ge (Frontiers in Environmental Science, 2022)
The Green credit policy is a crucial measure that Chinese government has adopted in their attempt to solve environmental problems through credit policies and environmental laws and regulations. This paper takes the Green Credit Guidelines issued in 2012 as a quasi-natural experiment to examine its impact on the export quality of firms. Using the sample cover Chinese A-share listed firms and the difference-in-difference method, the empirical research showed that the Green Credit Guidelines have significantly enhanced the export quality of firms. The mediation analyses have presented that green technology innovation is the intermediate channel for the Green Credit Guidelines to enhance the export quality of firms. The heterogeneity analysis of firm characteristics has demonstrated that the improvement effect brough by the Green Credit Guidelines is significantly reflected in state-owned firms and firms in financially underdeveloped areas. The research results of this paper provide a theoretical guidance on how to deal with environmental regulation for firms. Concurrently, it also serves as an important reference for global countries, especially the developing countries, on the successful implementation of green credit policies in order to achieve sustainable development.